MEMAHAMI TEKNOLOGI IT: FONDASI, SISTEM DAN KESEMPATAN KARIER - Muhamad Iksan; Wafa Zabira Revan; Melanie Putria; Darul Huda; Amir Rozy Sinaga; T.M. Aditya Ramadhan; Iddodo; Raihan Rizky Nurfadila; Ahmad Ismail; Rahmat Ibnu Iman (Shofanah Media Berkah, 2025)
Kegiatan pengabdian masyarakat dengan bertema